Metode Perbaikan Citra Naskah Kuno Menggunakan Histogram Terekualisasi Lokal dan Global - Baihaqi; Yeni Yanti; Malahayati (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Ancient manuscripts are precious relics of the past. These manuscripts are very susceptible to disturbances, including changes in the colour of the paper. For example, the paper may become dark and black (known as foxing), and there may be black spots due to exposure to water. These changes in paper colour can affect the comfort and legibility of the document. In order to preserve and protect these ancient manuscripts, any manuscript that shows signs of damage must be repaired. One effort to restore scanned ancient manuscripts involves the use of local and global image restoration methods based on histogram equalisation. In this research project, histogram equalisation is used to improve image quality by eliminating foxing and improving the contrast between text and background. Based on the Mean Opinion Score (MOS) values obtained from the tests, the histogram equalisation method is effective in eliminating foxing compared to the Otsu method